The effect of franchise no-poaching restrictions on worker earnings - Brian Callaci; Matthew Gibson; Sérgio Pinto; Marshall Steinbaum; Matt Walsh (W.E. Upjohn Institute for Employment Research, 2024)
We evaluate the nationwide impact of the Washington State attorney general's 2018-2020 enforcement campaign against no-poach clauses in franchising contracts, which prohibited worker movement across locations within a chain. Implementing a staggered difference-indifferences research design using Burning Glass Technologies job vacancies and Glassdoor salary reports from numerous industries, we estimate a 6 percent increase in posted annual earnings from the job vacancy data and a 4 percent increase in worker-reported earnings.
Keywords: J42; K21; L40; J31; 330; Employer market power; oligopsony; monopsony; franchising chains; antitrust; wages; salaries